How to attract international students? - Arnaud Chevalier (IZA World of Labor, 2022)
In knowledge-based economies, attracting and retaining international students can help expand the skilled workforce. Empirical evidence suggests that open migration policies and labor markets, whereby students can remain in the host country post-study, as well as good quality higher education institutions are crucial for successfully attracting international students. Student migration can positively affect economic growth in both sending and receiving countries, even though migrants themselves reap most of the gains, mainly through higher earnings.
Keywords: I23; I25; J61; 330; higher education; migration; study